Coptisine-induced inhibition of Helicobacter pylori: elucidation of specific mechanisms by probing urease active site and its maturation process. (1st January 2018) - Li, Cailan; Huang, Ping; Wong, Kambo; Xu, Yifei; Tan, Lihua; Chen, Hanbin; Lu, Qiang; Luo, Chaodan; Tam, Chunlai; Zhu, Lixiang; Su, Ziren; Xie, Jianhui
Abstract: In this study, we examined the anti- Helicobactor pylori effects of the main protoberberine-type alkaloids in Rhizoma Coptidis. Coptisine exerted varying antibacterial and bactericidal effects against three standard H. pylori strains and eleven clinical isolates, including four drug-resistant strains, with minimum inhibitory concentrations ranging from 25 to 50 μg/mL and minimal bactericidal concentrations ranging from 37.5 to 125 μg/mL. Coptisine's anti- H. pylori effects derived from specific inhibition of urease in vivo . In vitro, coptisine inactivated urease in a concentration-dependent manner through slow-binding inhibition and involved binding to the urease active site sulfhydryl group. Coptisine inhibition of H. pylori urease (HPU) was mixed type, while inhibition of jack bean urease was non-competitive. Importantly, coptisine also inhibited HPU by binding to its nickel metallocentre. Besides, coptisine interfered with urease maturation by inhibiting activity of prototypical urease accessory protein UreG and formation of UreG dimers and by promoting dissociation of nickel from UreG dimers. These findings demonstrate that coptisine inhibits urease activity by targeting its active site and inhibiting its maturation, thereby effectively inhibiting H. pylori . Coptisine may thus be an effective anti- H. pylori agent.